Some Lessons from the History of Epidemics in Africa - (:unkn) unknown (My University, 2020)
The history of endemic diseases, epidemics and pandemics in Africa shows, contrary to a stubborn belief, that the continent has had a long experience of biomedicine – its theory, techniques, and modes of action. Africans have been active in biomedicine, exercising methods of appropriation and implementation that are as ‘modern’ and effective as in the rest of the world. Like Westerners, they have a long experience in the theories of microbial contagion and modern prophylaxis and treatment, which appeared in the 1860s but did not become widespread until the turn of the twentieth century in Europe, coinciding with colonial expansion across Africa. During and after this period, Africa played an essential role in the discovery and treatment of many diseases such as malaria, trypanosomiasis (sleeping sickness), smallpox, syphilis, tuberculosis and plague (Packard 2007; Webb 2013). Major scientific institutions such as the Pasteur Institute in Paris (1887) and the London School of Hygiene and Tropical Medicine (1899) played a part in circulating imperial knowledge. Their role in the progress of research is increasingly studied by historians (Arnold 1996; Tilley 2012). The expertise of Africans, whether as researchers, caregivers, or ordinary consumers of biomedicine, is therefore comparable to that of the rest of the world. In many points, it is even superior; I will come back to this in my conclusion.[...]
Keywords: African Research